Retail Industry: Is It Needed the Balance Scorecard (BSC) to Maximize the Business? - Yuvita Ratnandika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this globalization era, business competition is becoming increasingly fierce, one of the industry that impact is retail industry, where each company is required to formulate dynamic strategies, one of which is through the implementation of performance measurement mechanisms that provide continuous control over the respective company. Through this research, author will identify through the literature can the Balanced Scorecard help the retail industry in their business. Some research already conduct for this balanced scorecard implementation in retail industry ? but this research will be focus on how balanced scorecard can help the retail industry create competitive strategy to maximize their business performance. This research uses systematic literature review to provide the right position in the direction of renewal into consideration regarding implementation Balanced Scorecard to maximize business in retail industry. This research finds that the retail category industry need use do some innovations and create their own competitive advantage to win and being sustain in the industry. This literature study still refers to the use of the classic Balanced Scorecard. Suggestions for research in the future, can use more updated Balanced Scorecard (third generation) to add more findings and to fill the gap in this research study